On the importance of 3D, geometrically accurate, and subject-specific finite element analysis for evaluation of in-vivo soft tissue loads - Moerman, Kevin M.; van Vijven, Marc; Solis, Leandro R.; van Haaften, Eline E.; Loenen, Arjan C. Y.; Mushahwar, Vivian K.; Oomens, Cees W. J. (Computer methods in biomechanics and biomedical engineering, 2017)
Pressure ulcers are a type of local soft tissue injury due to sustained mechanical loading and remain a common issue in patient care. People with spinal cord injury (SCI) are especially at risk of pressure ulcers due to impaired mobility and sensory perception. The development of load improving support structures relies on realistic tissue load evaluation e.g. using finite element analysis (FEA). FEA requires realistic subject-specific mechanical properties and geometries. This study focuses on the effect of geometry. MRI is used for the creation of geometrically accurate models of the human buttock for three able-bodied volunteers and three volunteers with SCI. The effect of geometry on observed internal tissue deformations for each subject is studied by comparing FEA findings for equivalent loading conditions. The large variations found between subjects confirms the importance of subject-specific FEA.